Acacia Changes Microbial Indicators and Increases C and N in Soil Organic Fractions in Intercropped Eucalyptus Plantations - Pereira, Arthur P. A.; Zagatto, Maurício R. G.; Brandani, Carolina B.; Mescolotti, Denise de Lourdes; Cotta, Simone R.; Gonçalves, José L. M.; Cardoso, Elke J. B. N. (Frontiers in Microbiology, 2018)
Intercropping forest plantations of Eucalyptus with nitrogen-fixing trees can increase soil N inputs and stimulate soil organic matter (OM) cycling. However, microbial indicators and their correlation in specific fractions of soil OM are unclear in the tropical sandy soils. Here, we examined the microbial indicators associated with C and N in the soil resulting from pure and intercropped Eucalyptus grandis and Acacia mangium plantations. We hypothesized that introduction of A. mangium in an Eucalyptus plantation promotes changes in microbial indicators and increases C and N concentrations on labile fractions of the soil OM, when compared to pure eucalyptus plantations. We determined the microbial and enzymatic activity, and the potential for C degradation by the soil-microbial community. Additionally, we evaluated soil OM fractions and litter parameters. Soil (0-20 cm) and litter samples were collected at 27 and 39 months after planting from the following treatments: pure E. grandis (E) and A. mangium (A) plantations, pure E. grandis plantations with N fertilizer (E+N) and an E. grandis and A. mangium intercropped plantations (E+A). The results showed that intercropped plantations (E+A) increase 3%, 45% and 70% microbial biomass C as compared to A, E+N and E, at 27 months after planting. The metabolic quotient (qCO2) showed a tendency towards stressful values in pure E. grandis plantations and a strong correlation with dehydrogenase activity. A and E+A treatments also exhibited the highest organic fractions (OF) and C and N contents. A canonical redundancy analysis revealed positive correlations between microbial indicators of soil and litter attributes, and a strong effect of C and N variables in differentiating A and E+A from E and E+N treatments. The results suggested that a significant role of A. mangium enhance the dynamics of soil-microbial indicators which help in the accumulation of C and N in soil organic fractions in intercropped Eucalyptus grandis plantations. Our results are mostly relevant to plantations in sandy soil areas with low levels of organic matter, suggesting and efficient method for improving nutrient availability in the soil and optimizing eucalyptus growth and development.